Self-esteem and body-image dissatisfaction among adolescents: A cross-sectional study - Meera George; Neethu George; S Ajmal; Aga Paul; M S Aathira; A K Amruthavani (Wolters Kluwer Medknow Publications, 2020)
Introduction: Adolescence is the time period in which the values about themselves will be created. Hence, self-esteem and correct perception about own body are an important context in their life. Objectives: The objective of this study is to find out the degree of dissatisfaction with their body size (DDBS) among adolescents and to analyze the influence of it on self-esteem. Material and Methods: This study was cross-sectional done among the undergraduate students in a private medical college and students of high-school section of the government school. A questionnaire was used to document the sociodemographic details, subjective assessment of body image, and self-esteem. Results: In this study, majority of the students had high (93; 50.8%) self-esteem and moderate self-esteem (62; 33.9%). Out of 183 samples, 53 (29%) were satisfied with body contour based on DDBS. In those who were underweight, it is shown that 48 (54.5%) wanted to increase their body weight, and in normal body mass index (BMI) category, 50% of participants wanted to lose their body weight. Age and BMI were significantly associated with self-esteem and body-image perception. Conclusion: The concept of body image has to be modified to reduce the risk of overweight, obesity, and eating disorders. This, in turn, can increase and sustain the self-esteem of adolescence.